Phytotoxic Effects of Polystyrene Microplastics on Growth Morphology, Photosynthesis, Gaseous Exchange and Oxidative Stress of Wheat Vary with Concentration and Shape - Komal Riaz; Tahira Yasmeen; Kotb A. Attia; Itoh Kimiko; Muhammad Saleem Arif (Toxics)
Microplastics pose a serious ecological threat to agricultural soils, as they are very persistent in nature. Microplastics can enter the soil system in different ways and present different shapes and concentrations. However, little is known about how plants react to microplastics with different concentrations and shapes. To this end, we conducted a factorial pot experiment with wheat (Triticum aestivum L.) in which we mixed polystyrene (PS) in different shapes (bead, fiber and powder) with soil at concentrations of 0, 1, 3 and 5%. Although all shapes of PS significantly reduced morphological growth traits, PS in powder shape was the microplastic that reduced plant height (by 58–60%), fresh biomass (by 54–55%) and dry biomass (by 61–62%) the most, especially at the 3% and 5% concentrations compared with 0% PS. Similar negative effects were also observed for root length and fresh root weight at the 3% and 5% concentrations, regardless of shape. A concentration-dependent reduction in the leaf area index (LAI) was also observed. Interestingly, increasing the PS concentration tended to up-regulate the activity of antioxidant enzymes for all shapes, indicating potential complexity and a highly time-dependent response related to various reactive oxygen species (ROS). Importantly, PS at the 5% concentration caused a significant reduction in chlorophyll pigmentation and photosynthetic rate. For the transpiration rate, stomatal conductance and intercellular CO2 concentration, the negative effects of PS on wheat plants increased with the increase in microplastic concentration for all shapes of PS. Overall, we concluded that PS microplastics at higher concentrations are potentially more devastating to the physiological growth and biochemical attributes of wheat, as evidenced by the negative effects on photosynthetic pigments and gas exchange parameters for all shapes. We recommend further research experiments not only on translocation but also on tissue-specific retention of different sizes in crops to fully understand their impact on food safety.